Can Service Design Enhance Employee-driven Innovation? - Jendbro,Sara; Essaidi,Fatima (2025)
This master thesis investigates the Service Design concept in connection to the Employee-driven Innovation (EDI) field. The Service Design concept entails both a mindset and a toolbox, involving principles such as human-centricity, collaboration and holistic understanding. Previous research has called for more structured approaches to the bottom-up innovation and the EDI process. Furthermore, researchers have argued that there is a need for tools which can facilitate the EDI work. Aiming to create such structured approaches and find relevant tools to utilize, this study examined how the Service Design concept can be incorporated into the EDI process and what behavioral implications such an incorporation would have. The study has been performed as a single-case study at FASA Tech, a large technology intensive company located in Sweden, using abductive reasoning and a qualitative approach. 21 semi-structured interviews have been conducted with FASA Tech employees, ranging from ‘ordinary’ employees, to product managers, directors and a C-level management representative. The empirical findings were analyzed based on the theoretical framework of the thesis, largely involving previous research on EDI and Service Design. Based on the empirical and theoretical findings, the study illustrated the importance of human guidance and support in the EDI process. In response to the employees being opposed to the idea of introducing the Service Design tools as a stand-alone concept, the authors suggest that Service Design can be introduced at the case company in the form of human innovation guides. Such guides could adopt the Service Design mindset and act as EDI enablers by, for instance, increasing the transparency in the idea selection process, ensuring strategic alignment of the EDI ideas and the company strategy and facilitating cross-departmental collaboration.
Keywords: Employee-driven Innovation; Service Design; Bottom-up Innovation; Human Support; Innovation Enablers; Innovation Challenges; Innovation Tools; Human Side of Innovation